2019
DOI: 10.3390/jcm8091373
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Pain Acceptance Predict Pain Outcomes in Interdisciplinary Treatment for Chronic Pain

Abstract: Studies have shown that pain acceptance is associated with a better pain outcome. The current study explored whether changes in pain acceptance in the very early treatment phase of an interdisciplinary cognitive-behavioral therapy (CBT)-based treatment program for chronic pain predict pain outcomes. A total of 69 patients with chronic, non-malignant pain (at least 6 months) were treated in a day-clinic for four-weeks. Pain acceptance was measured with the Chronic Pain Acceptance Questionnaire (CPAQ), pain outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Interdisciplinary approaches to pain concentrated on the biopsychosocial model. This model emphasizes psychological factors in pain perception, such as thoughts, emotions, and behaviors [ 1 3 ]. According to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), pain disorders form an independent classification of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Interdisciplinary approaches to pain concentrated on the biopsychosocial model. This model emphasizes psychological factors in pain perception, such as thoughts, emotions, and behaviors [ 1 3 ]. According to the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), pain disorders form an independent classification of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the more comprehensive and functional nature of the assessment of interference compared with average pain and pain severity. A prior study investigating chronic pain perception and acceptance found that early changes in pain acceptance were associated with key pain outcomes, yet not associated with pain intensity during the 4-week program [25]. Although changes in depression symptomology may not impact pain severity, they may be a robust indicator of how pain impacts everyday life.…”
Section: Discussionmentioning
confidence: 93%
“…Psychotherapy such as cognitive behavioural therapy (CBT) [35,36], acceptance and commitment therapy (ACT) [37,38], eye movement desensitisation and reprocessing (EMDR) [39], and "pain neuroscience education" (PNE) [33] has high significance internationally in the treatment of patients with pain, as mentioned in Section 4. It goes almost without saying that patients with lipoedema may also benefit from these approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Therapies that are well-researched in the field of interdisciplinary treatment include cognitive behavioural therapy (CBT) [35,36], which allows a breakthrough in the vicious circle of fear and avoidance, and attention-based acceptance and commitment therapy (ACT), which is used to increase psychological flexibility. Both of these therapies have effects on the severity of pain and improve depression and the quality of life [37,38].…”
Section: Effects Of Pain Education and Psychotherapy On Psychologicalmentioning
confidence: 99%